Continuous‐scan capability at SSRL and applications to X‐ray diffraction. (14th June 2016) - Li, Chunlei; Kiss, Andrew M.; Van Campen, Douglas G.; Garachtchenko, Alex; Kolotovsky, Yuriy; Stone, Kevin; Xu, Yahong; Zhang, Wenjun; Corbett, Jeff
Abstract : An integrated continuous‐scan system has been developed at the Stanford Synchrotron Radiation Lightsource (SSRL). The time efficiency and repeatability of the continuous‐scan system were tested using X‐ray diffraction from a ZnO powder and compared with the step‐scan technique. Abstract : Typical X‐ray diffraction measurements are made by moving a detector to discrete positions in space and then measuring the signal at each stationary position. This step‐scanning method can be time‐consuming, and may induce vibrations in the measurement system when the motors are accelerated and decelerated at each position. Furthermore, diffraction information between the data points may be missed unless a fine step‐scanning is used, which further increases the total measurement time. To utilize beam time efficiently, the motor acceleration and deceleration time should be minimized, and the signal‐to‐noise ratio should be maximized. To accomplish this, an integrated continuous‐scan system was developed at the Stanford Synchrotron Radiation Lightsource (SSRL). The continuous‐scan system uses an in‐house integrated motor controller system and counter/timer electronics. SPEC software is used to control both the hardware and data acquisition systems. The time efficiency and repeatability of the continuous‐scan system were tested using X‐ray diffraction from a ZnO powder and compared with the step‐scan technique. Advantages and limitations of the continuous‐scan system and a demonstration of variable‐velocity continuous scan are discussed.